THE INLFUENCE OF ENTREPRENEURIAL ORIENTATION, MARKET ORIENTATION, AND MARKETING CAPABILITY ON CULINARY SME PERFORMANCE IN BINTARO REGION - Waga, Robertus Krosihi Jaya; Widjaja, Oey Hannes (International Journal of Application on Economics and Business, 2024)
This research aims to determine the influence of entrepreneurial orientation, market orientation, and marketing capability on the performance of culinary MSME businesses in Bintaro Sector 9. The method used in this research is a quantitative research method and the data collection method used is distributing questionnaires to 80 respondents who are MSMEs in the culinary sector in Taman Jajan Bintaro using a non-probability sampling technique carried out using a purposive sampling approach. The program used to process the data that has been received is the SmartPLS 4 program with a bootstrapping procedure to measure the level of significance. The results obtained in this research indicate that entrepreneurial orientation, market orientation, and marketing capability have a positive and significant effect on the performance of MSMEs.